Using quantitative analysis to identify binding development constraints and options for their alleviation - two case studies in health and vocational training in Zambia - Mwenge, Felix (Graduate School of Development Policy and Practice, 2017)
This report is a quantitative analysis of two case studies demonstrating the binding development constraints and options for their alleviation. The first case study is an analysis of health inequalities which remain an important policy issue in many developing countries. Using the 2014 data for the Zambia Demographic and Health Survey (DHS), the paper assesses health inequality in Zambia using Child stunting as a health variable. The paper finds that those in the poorest group had more than thrice the Child stunting rate of the richest group, proving the existence of health inequality in Zambia. The paper further investigates the factors associated with stunting and finds that the mother's age, education, marital status, socio-economic status, location and nutritional status measured by body mass index (BMI) are significantly associated with Child stunting. Policy recommendations center on women empowerment, improving household food security and rolling out Social Cash Transfer schemes among others. The second case study is concerned with technical and vocational skills development, which despite being a key factor in economic growth remains limited in Zambia. Using multiple regression, the study finds that participating in skills training is determined by age, level of education, gender and location (rural or urban). These factors also affect participants' choices among the various skills training options that exist in Zambia: on-the-job training, public institutions, private institutions and apprenticeship. The study provides a number of recommendations. One relates to improved access to education for girls to improve their chances of accessing skills training. Another one calls for the formalisation of apprenticeships which remain informal and unofficial despite a substantial proportion of people acquiring skills through this avenue.